1990
DOI: 10.1046/j.1537-2995.1990.30590296378.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemolysis after intravenous immune globulin therapy: relation to IgG subclasses of red cell antibody

Abstract: A patient with chronic idiopathic thrombocytopenic purpura (ITP), a 28-year-old group A, Rh-positive woman, also had hemolytic anemia. At that time, her red cells typed as group A, but the serum typed as group O. This typing followed intravenous high-dose immune globulin therapy, (400 mg/kg for 5 successive days) and was attributable to A antibody of the IgG type, composed of IgG1, IgG2, IgG3, and IgG4, in the immune globulin preparation, which had been given for treatment of ITP. All lots of commercial human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…In the preparation of IVIg, these IgG isoantibodies form part of the pooled IgG. Although the titers of IgG isoantibodies in IVIg have not, for the most part, been considered a problem, there have been reports of hemolysis subsequent to IVIg in type A or B recipients [15, 16]. We have shown that the anti–A and anti–B in IVIg are sufficient to bind to RBC and mediate erythrophagocytosis.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…In the preparation of IVIg, these IgG isoantibodies form part of the pooled IgG. Although the titers of IgG isoantibodies in IVIg have not, for the most part, been considered a problem, there have been reports of hemolysis subsequent to IVIg in type A or B recipients [15, 16]. We have shown that the anti–A and anti–B in IVIg are sufficient to bind to RBC and mediate erythrophagocytosis.…”
Section: Discussionmentioning
confidence: 86%
“…Such treatment can bring about subclinical sequestration of erythrocytes in normal healthy persons [9], and can induce [11, 12, 13, 14, 16, 17, 18, 19, 24, 25]or exacerbate hemolytic anemia in treated patients [9, 10, 15]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus RBC antibodies have been found in 49 percent of 165 lots of IVIG, including anti‐K, ‐C, and ‐Le b 160 . Most antibodies detected in IVIG are low titer (<1:16, using a saline method; <1:1024 using an antiglobulin method) 171,172 . Nonetheless, positive antibody screens and DATs in patients treated with IVIG are seen, although limited in duration (2‐5 days) 173 ‐175 .…”
Section: Passive Transfer Of Blood Group Antibodiesmentioning
confidence: 99%